Development, Optimization, and Field Evaluation of the Novel Collapsible Passive Trap for Collection of Mosquitoes. Issue 3 (29th January 2018) - Meyer, Dagmar B; Johnson, Brian J; Fall, Ken; Buhagiar, Tamara S; Townsend, Michael; Ritchie, Scott A
Abstract: Disease surveillance for mosquito-borne pathogens in remote areas can be challenging. Most traps used to collect mosquitoes either need a source of electricity or are bulky and inflexible, making transportation awkward. To reduce these issues we developed three Collapsible Passive Traps (CPTs) and conducted trials in Cairns, Australia to evaluate the optimal design for a CPT and compared them to traditionally-used traps such as Centers for Disease Control and Prevention (CDC) and Encephalitis Vector Surveillance (EVS) light traps. We found that two of the CPTs collected comparable numbers of mosquitoes and that one of the CPTs outperformed the CDC light trap in collecting Aedes species. Mosquitoes did not have to pass through a fan while entering the CPT, and thus were not damaged and were often alive. Our results suggest that the CPT can be an effective trap for mosquito surveillance, especially in remote areas.